Morphofunctional Сhanges of Gallbladder and Biochemical Parametеrs of Lipid Metabolism in Children with Liver Steatosis - S.O. Babii; N.Yu. Zavgorodnya; I.S. Konenko (Zaslavsky O.Yu., 2016)
Background. The aim of study was to investigate peculiarities of structural and functional disorders of gallbladder in children with non-alcoholic fatty liver disease. Materials and methods. The study was conducted in 51 children aged 10-17 years. Patients were divided into four groups: the 1st group consisted of 11 children with biliary normokinesia without steatosis; the 2nd group - 20 children with biliary hypokinesia without steatosis; 3rd group - 11 children with biliary normokinesia and steatosis, and the 4th group - 9 children with biliary hypokinesia and steatosis. Anthropometric parameters were measured: height, weight, abdominal circumference, body mass index. Functional state of gallbladder was investigated with the help of ultrasound. Such biochemical parameters, as total cholesterol, triacylglycerols, levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and very-low-density lipoprotein cholesterol were defined, atherogenic index was calculated according to Friedewald formula. Results. Present study shows overweight (in 15 % of patients), obesity (in 85 % of patients), increase in the gallbladder volume by 30-50 % (p < 0.05), in the density of gallbladder wall by 12-16 % (p < 0.05) and its echogenicity by 24 % (p < 0.05) in children with steatosis versus group without steatosis and gallbladder normokinesia. Positive correlation between wall thickness and steatosis has been established. Thus, weight increase may potentially play a role in lipid disorders and biliary dysfunction. The 70 % of children with obesity had pathological changes of lipid levels, such as 74 % - increased blood atherogenicity. Conclusions. Physicians must necessarily correct a functional state of gallbladder during the treatment of obesity in children and adolescents. Only comprehensive approach to the treatment allows prevention of non-alcoholic fatty liver disease and its complications.